Evaluation of antiplasmodial activity and cytotoxicity assays of amino acids functionalized magnetite nanoparticles: Hyperthermia and flow cytometry applications - Rodriguez, Anselmo F.R.; dos Santos, Caio C. [UNESP]; Lüdtke-Buzug, K.; Bakenecker, Anna C.; Chaves, Yury O.; Mariúba, Luis A.M.; Brandt, João V. [UNESP]; Amantea, Bruno E. [UNESP]; de Santana, Ricardo C.; Marques, Rodrigo F.C. [UNESP]; Jafelicci, Miguel [UNESP]; Morales, Marco A. (Elsevier, 2021)
We report the synthesis of magnetite nanoparticles (MNP) and their functionalization with glycine (MNPGly), β-alanine (MNPAla), L-phenylalanine (MNPPhAla), D-(−)-α-phenylglycine (MNPPhGly) amino acids. The functionalized nanoparticles were characterized by Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray diffraction (XRD), electron paramagnetic resonance (EPR), vibrating sample magnetometry (VSM), Mössbauer spectroscopy (MS), magnetic hyperthermia (MH), dynamic light scattering and zeta potential. The functionalized nanoparticles had isoelectric points (IEP) at pH ≃ 4.4, 5.8, 5.9 and 6.8 for samples MNPGly, MNPAla, MNPPhGly and MNPPhAla, respectively, while pure magnetite had an IEP at pH 5.6. In the MH experiments, the samples showed specific absorption rate (SAR) of 64, 71, 74, 81 and 66 W/g for MNP, MNPGly, MNPAla, MNPPhGly, and MNPPhAla, respectively. We used a flow cytometric technique to determine the cellular magnetic nanoparticles plus amino acids content. Magnetic fractionation and characterization of Resovist® magnetic nanoparticles were performed for applications in magnetic particle imaging (MPI). We have also studied the antiproliferative and antiparasitic effects of functionalized MNPs. Overall, the data showed that the functionalized nanoparticles have great potential for using as environmental, antitumor, antiparasitic agents and clinical applications.
Keywords: Amino acids; Flow cytometry; Magnetic hyperthermia; Nanoparticles; Nanotoxicology